Assessment of Teachers’ Knowledge and Practices on Laboratory Waste Disposal - Lezondra, Micheal (SEAQIS Journal of Science Education, 2024)
In alignment with the United Nations Sustainable Development Goals 2030 (UN SDGs 2030), which emphasise the importance of ensuring education inclusivity and quality for all, this study investigated the quality of education in the context of science teachers’ knowledge and practice related to laboratory waste disposal. Understanding the critical role that science teachers have in fostering a safe and sustainable learning environment, the research focused on the gap between the awareness and application of proper laboratory waste management techniques. Filling this gap is imperative not only for the well-being of the school community but also for the contribution to the broader goals of sustainable development outlined in the UN SDGs 2030. Consequently, this study assessed teachers’ knowledge and practice in handling laboratory waste disposal. As a qualitative research, this study used a phenomenological design with semi-structured interviews using open-ended questions to gather data from 20 public science teachers from Santa Rosa City and Cabuyao City in Laguna Province as respondents. Regarding teachers’ knowledge, three themes emerged, namely: (1) recycling techniques, (2) waste segregation and disposal, as well as (3) treatment of laboratory waste. However, the majority of science teachers admit that they have limited knowledge of how laboratory waste should be disposed of. They tended to apply basic knowledge of waste management that they already knew, despite being aware that laboratory waste should be treated differently from solid waste generated by our offices at schools. Teacher’s practice on laboratory waste disposal involved three steps, including identification, segregation of laboratory waste, and laboratory waste management disposal. Unfortunately, all were found to be inadequate to maintain proper laboratory waste disposal at schools. Hence, this study highlights the need to enhance awareness and facilitate training on laboratory waste disposal among teachers in public schools. Specific training and education on laboratory waste management, treatment, and disposal are essential for teachers in public schools who work in laboratory settings. Regular monitoring and evaluations of teachers’ laboratory waste disposal practices should also be implemented to ensure that they adhere to the proper procedures